대건중탕 및 쑥뜸치료로 호전된 간세포암 환자의 암성 통증 1례 - 이수정; 하정빈; 유재환; Lee, Su-jung; Ha, Jeong-been; Lew, Jae-hwan (大韓癌韓醫學會誌, 2020)
Objective: Most cancer patients suffer from various forms of pain. This study presents the case of a patient with hapatocellular carcinoma with abdominal pain treated by Daegunjoong-tang. Method: For 7 days, the patient was treated with Daegunjoong-Tang and Moxibustion. We planned to maintain moxibustion CV12(中脘), CV4(關元) for 20 minutes everyday. To evaluate the therapeutic effect, we used Visual Analogue Scale (VAS) and Clinical Opiate Withdrawal Scale (COWS). Results: After the treatments, Visual Analogue Scale (VAS) and Clinical Opiate Withdrawal Scale (COWS) score about abdominal pain are decreased. Conclusions: These results suggested that Daegunjoong-tang and Moxibustion have a beneficial effect on relieving abdominal pain caused by cancer.